2007
DOI: 10.5339/qmj.2007.2.13
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Five Year Experience in Amniocentesis in Qatar

Abstract: Objective: The purpose of this study is to evaluate the risk of foetal loss attributable to amniocentesis and to assess the experience in technique, successful fluid aspiration in amniocentesis performed in our hospital Study Design: Medical record of 123 women who underwent amniocentesis between September 1996 till March 2002 were reviewed for indication, maternal, age, nationality, maternal age, parity, nationality, gestational age at procedure, physician operator, amniotic fluid reports and pregnancy outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The overall aspiration success rate was 100%, which is similar to the study of 144 amniocenteses by Ahmed, and higher success rate than the study of Tamimi, who reported the success rate of 96.8%. 15,16 Bleeding and spotting are not very common, although Abeera et al have reported haematoma formation in 1.5% cases and vaginal bleeding in 0.5% cases. 17 We experienced the same minor complications like placental hematoma, per vaginal bleeding, minor intra-amniotic bleeding occurred in 7.1%, 2.8% and 2% cases respectively which were subsided by conservative management.…”
Section: Discussionmentioning
confidence: 99%
“…The overall aspiration success rate was 100%, which is similar to the study of 144 amniocenteses by Ahmed, and higher success rate than the study of Tamimi, who reported the success rate of 96.8%. 15,16 Bleeding and spotting are not very common, although Abeera et al have reported haematoma formation in 1.5% cases and vaginal bleeding in 0.5% cases. 17 We experienced the same minor complications like placental hematoma, per vaginal bleeding, minor intra-amniotic bleeding occurred in 7.1%, 2.8% and 2% cases respectively which were subsided by conservative management.…”
Section: Discussionmentioning
confidence: 99%